2016
DOI: 10.1186/s12864-016-2802-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting genotyping by sequencing to characterize the genomic structure of the American cranberry through high-density linkage mapping

Abstract: BackgroundThe application of genotyping by sequencing (GBS) approaches, combined with data imputation methodologies, is narrowing the genetic knowledge gap between major and understudied, minor crops. GBS is an excellent tool to characterize the genomic structure of recently domesticated (~200 years) and understudied species, such as cranberry (Vaccinium macrocarpon Ait.), by generating large numbers of markers for genomic studies such as genetic mapping.ResultsWe identified 10842 potentially mappable single n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 91 publications
(143 reference statements)
1
50
0
Order By: Relevance
“…Georgi et al (2013) published the first SSRbased genetic map of American cranberry, and reported several QTLs for yield, fruit weight, titratable acidity and proanthocyanidin content. With the recent development of high-density genetic maps (Schlautman et al 2015, 2017; Covarrubias-Pazaran et al 2016a; Daverdin et al 2017), the creation of new mapping populations (Schlautman et al 2015), the development of modern massive phenotyping techniques (Houle et al 2010), and the availability of the cranberry genome (Polashock et al 2014), the identification and fine-mapping of loci governing major phytochemicals in cranberry fruit are crucial for the future breeding of cultivars with enhanced phytochemical properties for processing and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Georgi et al (2013) published the first SSRbased genetic map of American cranberry, and reported several QTLs for yield, fruit weight, titratable acidity and proanthocyanidin content. With the recent development of high-density genetic maps (Schlautman et al 2015, 2017; Covarrubias-Pazaran et al 2016a; Daverdin et al 2017), the creation of new mapping populations (Schlautman et al 2015), the development of modern massive phenotyping techniques (Houle et al 2010), and the availability of the cranberry genome (Polashock et al 2014), the identification and fine-mapping of loci governing major phytochemicals in cranberry fruit are crucial for the future breeding of cultivars with enhanced phytochemical properties for processing and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Although the present composite map anchored 1500 more nuclear scaffolds than the previous SNP linkage map, those 1500 scaffolds only represented a 1.9% increase in the total megabases of cranberry genome anchored (Covarrubias-Pazaran et al 2016). This is reflective of the sheer number of scaffolds ( i.e.…”
Section: Discussionmentioning
confidence: 69%
“…aSNP loci with >20% missing data were excluded.bSNP loci with a MAF <10% were excluded.cSNP loci with extreme segregation distortion were excluded.dGenerated in Covarrubias-Pazaran et al (2016).eGenerated in Schlautman (2015a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that linkage decay occurs rapidly, at ?200 bp in wild Helianthus species and at 1100 bp in cultivated H. annuus lines (Liu and Burke, 2006;Mandel et al, 2011). Given the rapid linkage decay, approaches in which linkage blocks are maintained to a greater degree through consanguinity such as through family-based association mapping approaches (Guo et al, 2013) or pseudo-testcross approaches such as those used in other outcrossing species (Zhang et al, 2016;Covarrubias-Pazaran et al, 2016) may be appropriate in Maximilian sunflower. Although several wild annual Helianthus species are reported as being highly syntenic with H. annuus (Barb et al, 2014), the degree of structural chromosomal rearrangements between cultivated H. annuus and the perennial H. maximiliani is currently uncharacterized, which may influence the inference of linkage decay.…”
Section: Snp Yield and Linkage Disequilibriummentioning
confidence: 99%